Dampak Remitansi terhadap Investasi Domestik: Analisis Peranan Perkembangan Sektor Keuangan dan Kualitas Institusi pada Emerging Market di Negara-Negara Asia - Heki Wilastra (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
Remittances is one of the largest capital inflows in emerging markets Asia after FDI. This study investigates the impact of remittances on domestic investment in Asian emerging market countries. A panel domestic investment model uses remittances, financial development and institutional quality. The interaction variables between remittances, financial development and institutional quality are also added to see the joint effects of these variables. The panel data approach used includes slope heterogeneity, cross-section dependence, unit root panel, cointegration panel and FMOLS which takes into account the potential for heterogeneity and endogeneity. The period considered were 1998 – 2019. This study’s outcomes show that increasing of remittance inflows led to decline in domestic investment and confirmed the dutch disease phenomenon. However, joint effect of remittances and financial development and also institutional quality is positive and nullflies the dutch disease phenomenon. In addition, increased of financial development and institutional quality may foster domestic investment.